Gastro-esophageal reflux and obstructive sleep apnea – is there a link? - Pardak, Piotr; Pękala, Anna; Jarmakiewicz, Sara; Filip, Rafał (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. The epidemic of obesity has led to an increase in the occurrence of obstructive sleep apnea and gastro-esophageal reflux disease. The mechanism of development of gastro-esophageal reflux disease is multifactorial, and studies conducted in the last decade have shed new light on the causes of its development in patients with sleep apnea and obesity. Aim. The aim of the study was to discuss the mechanism of development of gastro-esophageal reflux disease is multifactorial, and studies conducted in the last decade have shed new light on the causes of its development in patients with sleep apnea and obesity and the dysfunction of the lower esophageal sphincter. Material and methods. An analysis of literature regarding gastro-esophageal reflux and obstructive sleep apnea. Results. In obstructive sleep apnea and obesity, high levels of cytokines and insulin resistance are observed, resulting in disorders in the levels of ghrelin – a hormone responsible for normal gastrointestinal motility. Conclusion. The effect of deviations in the ghrelin profile on the development of gastro-esophageal reflux disease remains a matter for further research.
Keywords: gastro-esophageal reflux; ghrelin; obesity; obstructive sleep apnea